Evaluating the impacts of xylo-oligosaccharides on growth performance of broiler chickens: A meta-analytical study - M. Naeem; Dianna Bourassa; Samuel Rochell; Mike Bedford (Journal of Applied Poultry Research)
Summary: This meta-analytical study evaluated the impacts of xylo-oligosaccharide (XOS) supplementation on the growth performance of broiler chickens using data from 36 peer-reviewed studies, published between 2000 and 2024. The parameters analyzed included average daily gain (ADG), average daily feed intake (ADFI), and feed conversion ratio (FCR). Results demonstrated that XOS supplementation increased (P < 0.05) ADG by 6.445 % and ADFI by 1.544 %, and decreased (P > 0.05) FCR by 7.147 %, compared to the control. Furthermore, XOS supplementation reduced the coefficient of variation (CV%) for ADG, ADFI, and FCR by 9.386 %, 5.759 %, and 4.037 %, respectively, indicating enhanced consistency in growth performance. Correlation analysis revealed a significant positive association between XOS levels and both ADG (R2 = 0.023, P = 0.031) and ADFI (R2 = 0.038, P = 0.009), while FCR showed no significant correlation (R2 = 0.004, P = 0.391). A predictive model for ADG (R² = 0.850, RMSE = 0.135) accounted for 85 % of the variation and demonstrated reliability through cross-validation, making it a robust for forecasting growth performance based on XOS inclusion rates. The model also highlighted significant interactions between XOS levels and ADFI, suggesting that the effects of XOS are influenced by feed intake. These findings underscore the potential of XOS to optimize broiler productivity and sustainability. However, the variability in efficacy due to dietary composition, XOS purity, and environmental conditions warrants further investigation.